PENGARUH VARIASI KADAR PEREKAT TAPIOKA TERHADAP KARAKTERISTIK BRIKET ARANG LIMBAH KAYU SENGON (Falcataria mollucana): The Influence of Adhesive Content Variation on the Characteristics of Sengon (Falcatataria moluccana) Wood Charcoal Briquettes - Siti Mutiara Ridjayanti; Wahyu Hidayat; Rahmi Adi Bazenet; Irwan Sukri Banuwa; Melya Riniarti (Forestry Faculty of Universitas Hasanuddin, 2021)
Biomass waste that has not been utilized properly is wood waste from Sengon (Falcataria moluccana). There is a high potential for these wastes to be used as solid fuel. The quality can be further improved by converting them into charcoal briquettes. This study aimed to determine the effects of adhesive content on the bioenergetic properties of charcoal briquette from sengon wood wastes. Sengon wood waste charcoal was produced with a pyrolysis method at a temperature of > 500 ℃. The charcoal briquettes were produced by mixing charcoal powders with tapioca starch with 5%, 10%, and 15%. The mixed charcoal powders and adhesives were then put into a metal cast and pressed using a Universal Testing Machine (UTM) Testometric M500-50AT under compression of 2,59-5,17 N/mm2 and a target density of 0,5 g/cm3. Biomass briquettes from sengon wood particles were also produced for comparison. The results showed oven-dry density of 0,23-0,25 g/cm3 and 0,18-0,20 g/cm3, for charcoal briquettes and biomass briquettes, respectively. Higher adhesive content increased the density of briquettes. Charcoal briquettes were more hydrophobic than biomass briquettes (control), showing a lower moisture content than control samples. The results of proximate analysis of charcoal briquettes showed volatile matter of 24,96–31,80%; ash content of 3,16–3,24%; and fixed carbon of 58,68–66.40%. Higher adhesive content increased the volatile matter, moisture content, and ash content of the charcoal briquettes and decreased the fixed carbon. The charcoal briquettes have a calorific value of 25,68-27,35 MJ/kg (6.137,67- 6.536,80 cal/g), which is remarkably higher than the control. Higher adhesive content tended to decrease the calorific value of the charcoal briquettes. Lower adhesive content will produce briquettes with good bioenergy characteristics. Sengon wood waste charcoal briquettes with 5% adhesive content have great potential to be developed as an alternative energy source.